Preclinical pharmacokinetic characterization of (R)-ketamine injection, a novel antidepressant glutamatergic agent - Wang, Rui; Jin, Yongchao; Zou, Bingjie; Ding, Li (Frontiers in Pharmacology, 2025)
IntroductionKetamine is a significant class of antidepressant drugs, and the pharmacokinetic and pharmacodynamic characteristics of its enantiomers exhibit differences. Among them, intravenous infusion of (R)-ketamine can effectively alleviate depressive symptoms in patients, offering the advantages of prolonged duration of action and minimal side effects. The extensive preclinical pharmacokinetic (PK) studies of (R)-ketamine were conducted to support its further development.MethodsThis study investigated the preclinical pharmacokinetic behavior of (R)-ketamine across different dose groups through single- and multiple-dose pharmacokinetic studies in rats and dogs, along with tissue distribution studies in Sprague-Dawley (SD) rats.In vitro metabolism study using microsomes from mice, rats, dogs, monkeys, and humans were conducted to evaluate metabolic stability and obtain metabolite profiles. The excretion studies in rats (7.5 mg/kg dose group) were performed to elucidate the primary elimination pathways of (R)-ketamine. The allometric scaling approach was employed to predict human plasma total clearance based on preclinical data.Results(R)-ketamine exhibits nonlinear pharmacokinetics in SD rats and Beagle dogs, with plasma exposure increasing disproportionately to dose after both single and multiple intravenous administrations. The highest tissue exposure to (R)-Ketamine was found in the fat and kidney of the rats. The (R)-ketamine concentration ratio of brain/plasma was 2.25 for the rats, indicating effective blood-brain barrier penetration and significant brain distribution of (R)-ketamine. (R)-ketamine undergoes rapid metabolism in liver microsomes from mice, rats, dogs, monkeys and humans. The predominant metabolite identified in human, monkey and mice liver microsomes was (R)-norketamine and demethylated and mono-oxidized metabolites in rats and dogs. (R)-ketamine is primarily excreted via bile, accounting for 3.613% of the dose within 72 h, significantly higher than in feces (0.327%) or urine (0.030%). The main elimination pathway may be metabolic elimination, and eventually excreted in the form of metabolites. The predicted human plasma total clearance of 29.93 mL/min/kg is close to reported value.ConclusionThe preclinical pharmacokinetic characteristics of (R)-ketamine injection have been thoroughly investigated, and these findings can provide valuable information for predicting the first-in-human dose and designing Phase I clinical trials for (R)-ketamine injection.